2015
DOI: 10.21767/2172-0479.100030
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety in Pediatric Population: Anesthesiologist"s Nightmare

Abstract: Surgery in a child is one of the most important events of its life. Exposure to hospital environment including operating room away from own area of comfort, meeting with new peoples and visualising sick people in agony creates a significant impact on a child's mind. Any unfavourable experience in this circumstance not only creates a fear towards medical systems for the lifetime but also sometimes lead to serious psychological consequences like post-traumatic stress disorders. The perioperative period is partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
6
0
3
Order By: Relevance
“…Such programs are efficient in decreasing anxiety, increasing understanding to health problem, facilitating communication with health care providers, and promoting recovery (Banchs & Lerman, 2014;He et al, 2015;Tanaka et al, 2011). For parents, preparation of children for surgery may increase their satisfaction with care provided to their children (Kar, Ganguly, Dasgupta, and Goswami, 2015).…”
Section: Preoperative Preparation Programsmentioning
confidence: 99%
“…Such programs are efficient in decreasing anxiety, increasing understanding to health problem, facilitating communication with health care providers, and promoting recovery (Banchs & Lerman, 2014;He et al, 2015;Tanaka et al, 2011). For parents, preparation of children for surgery may increase their satisfaction with care provided to their children (Kar, Ganguly, Dasgupta, and Goswami, 2015).…”
Section: Preoperative Preparation Programsmentioning
confidence: 99%
“…Induksi anestesi pada sebagian besar anak dapat menjadi keadaan dengan tingkat ketegangan yang tinggi. 1,3,4 Kecemasan pada anak selama periode perioperatif terjadi lebih dari 60% anak. Kecemasan preoperatif menyebabkan efek samping negatif pascaoperasi.…”
Section: Pendahuluanunclassified
“…There is a high global incidence of pediatric surgery (Czauderna et al, 2017;Jesus et al, 2009;Somme et al, 2013), and minimizing surgery anxiety and fear is among the many challenging tasks faced by nursing, surgery, and anesthesiology teams (Kar et al, 2015;Weber, 2010). The approach of the operating room nurse can minimize some of the negative aspects of hospitalization, including fear of surgery, anesthesia, and the unknown (Landier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports state that most children have varying degrees of anxiety during the immediate preoperative period (Carnier et al, 2015;Kar et al, 2015;Paladino et al, 2014). One study that addressed the coping strategies of 58 children aged 7-12 years old in a presurgical situation found that surgery was a stressful situation for half of the children and 77% of parents (Carnier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%